Genetic profiling of extended-spectrum β-Lactamase and carbapenemase-producing Escherichia coli O157:H7 from clinical samples among diarrheal patients in Shashemene, Ethiopia - Shimelis Teshome Ayalneh; Biruk Yeshitela Beshah; Yeonji Jeon; Ashenafi Alemu Wami; Seifegebriel Teshome; Solomon Gebreselassie; Se Eun Park; Mekonnen Teferi; Woldaregay Erku Abegaz (BMC Infectious Diseases)
Abstract Background Escherichia coli (E. coli) O157:H7, associated with diarrhea, poses a global health risk. In Ethiopia, where diarrhea is common, there is limited knowledge about these resistant strains and a lack of data on Extended-Spectrum β-Lactamase (ESBL) and carbapenemase production. Understanding the prevalence of antimicrobial resistance genes associated with ESBL and carbapenems is crucial for addressing diarrheal disease. This study aimed to investigate the genetic profile of ESBL and carbapenemase coding gene carriage in E. coli O157:H7 from clinical stool samples and evaluate antimicrobial susceptibility patterns. Methods A total of twenty-nine bacterial isolates obtained from diarrheal patients were subjected to conventional culture and phenotypic (Kirby Bauer disc diffusion method) testing for antimicrobial resistance. Additionally, screening for the production of ESBL (combined disk method) and carbapenemase (modified carbapenem inactivation method) was conducted. Isolates that tested positive for ESBL and carbapenemase production were further analyzed, targeting five genes (bla NDM, bla KPC, bla CTX−M, bla TEM, and bla SHV) associated with ESBL and carbapenemase production. Data analysis was performed using SPSS version 27.0, employing logistic regression and descriptive statistics. Results We analyzed a total of 27 isolates that were ESBL-positive and 12 isolates that were found to produce carbapenemase phenotypically. These isolates were obtained from clinical stool samples and (9/27) 33.3% of the isolates were from under five years children, predominantly from urban areas, and those that have contact with domestic animals. Genes coding ESBL were found in (19/27) 70.4% of the isolates, the most predominant being bla CTX−M and bla TEM. Eight isolates carried bla KPC, but none had bla NDM, while five isolates carried both bla CTX−M and bla TEM genes. bla SHV-carrying isolates showed phenotypic resistance to ampicillin and cephalosporins, while bla KPC-carrying isolates exhibited resistance to ampicillin, carbapenems, and tetracycline. Conclusion This study identifies a significant prevalence of multidrug resistance in E. coli O157:H7, which can be attributed to the presence of resistance genes coding for ESBL and carbapenem production. Key factors contributing to this resistance, such as urban environments, children under the age of five, and domestic animal ownership, have been emphasized. Additionally, this research underscores the urgent need for enhanced surveillance and targeted interventions to address this pressing public health concern.